Intracranial pressure changes during continuous renal replacement therapy in acute period of severe traumatic brain injury - A. A. Polupan; T. M. Birg; A. V. Oshorov; A. A. Pashin; Ya. A. Latyshev; I. A. Savin (Вестник анестезиологии и реаниматологии, 2023)
The objective was to study the effect of continuous renal replacement therapy (CRRT) in the acute period of traumatic brain injury (TBI) on intracranial pressure (ICP).   Materials and methods. An analysis of the dynamics of ICP during CRRT in patients with severe TBI was performed. The division of procedures into three groups, depending on the variant of ICP change, allowed to perform a comparative analysis of a number of factors that were potential predictors of aggravation of intracranial hypertension.   Results. During CRRT, ICP decreased in 39 % of cases (Group 1) and increased in 29 % of cases (Group 2). In 32 % of cases (Group 3), ICP did not change significantly during the procedure. The initial sodium level and the degree of sodium decrease during the first 6 hours of the procedurediffered between the groups, which turned out to be significantly higher in the group 2. An inverse correlation was found between the change in sodium level during the first 6 hours of the procedure and the change in ICP.   Conclusions. CRRT in the acute period of severe TBI can be associated with both a decrease and increase of ICP. The main risk factor for worsening intracranial hypertension during CRRT is hypernatremia.